Cross–cultural Validity of the Reactive–Proactive Aggression Questionnaire Among Adults Across Five Countries - Dinić, Bojana M. (Journal of interpersonal violence, 2022)
This study aims to test psychometric properties and factor invariance of the Reactive?Proactive Aggression Questionnaire (RPQ) for adults across five countries: Serbia (N = 409), Mauritius (N = 400), the United States (N = 389), the Netherlands (N = 372), and China (N = 325). The results supported the two?factor structure across country samples, with a marginal model fit in Mauritius. Results also supported the congruent factor structure of Reactive Aggression scale across countries, while the Proactive Aggression scale can be considered as equal across samples from Serbia, the United States, and China, but not from Mauritius and the Netherland. Among items from the Proactive Aggression scale, those referring to open aggression aimed at obtaining social status and dominance, frightening or harming others, obtained the highest loadings across all samples and could be considered as the good representatives of adult proactive aggression. This is the first study in which cross-cultural validation of the RPQ among adults has been tested and results suggested that there are some cultural differences in expression of proactive aggression.